FATIGUE LIFE EVALUATION OF DIFFERENT HIP IMPLANT DESIGNS USING FINITE ELEMENT ANALYSIS - Valerian Corda, John; N , Chethan K; B, Satish Shenoy; Shetty , Sawan; N , Shaymasunder Bhat; Zuber , Mohammad (Journal of Applied Engineering Science, 2023)
Fatigue failure is one of the causes of the failure of hip implants. The main objective of this work is to carry out fatigue failure analysis on different hip profiles and compare the outcomes for various combinations of materials. Three profiles each for circular, oval, elliptical, and trapezoidal stems are utilized for this study with four different material combinations consisting of materials like Ti–6Al–4V, CoCr Alloy and UHMWPE. CATIA V-6 is used for the modelling of these implants and the fatigue analysis using Goodman's mean stress theory is simulated using ANSYS 2022 R1. ISO 7206-4 and ASTM F2996-13 standards are used to define the boundary conditions. A total of 48 combinations were studied across four different shapes, three different profiles and four different material combi-nations to deduce the best possible combination for a hip implant for static and fatigue loading. Comparison of the implants is based on the factors like equivalent von Mises stress, displacement, equivalent elastic strain, fatigue life, safety factor and equivalent alternating stress. Profile 2 of the trapezoidal-shaped hip implant with a Ti–6Al–4V stem exhibited superior results both under static and fatigue loading conditions. Compared to displacements obtained for profiles one and three, profile 2 trapezoidal stem with Ti–6Al–4V and other parts as CoCr Alloy has about 72% lower displacement. Based on the findings, profile 2 with a trapezoidal stem made of Ti–6Al–4V and an acetabular cup made of CoCr shows the enhanced results over the other combinations considered.
Keywords: total hip arthroplasty, fatigue, finite element analysis, implants, displacement